Shunt active Power Filter Performance Evaluation Using Artificial Neural Networks (International Journal of Food and Nutritional Sciences, 2021)
Objective: This paper explores the power condition abilities of Shunt Hybrid Power Filter (SHPF) with fuzzy tuned PI based control method in a distribution system. Method: A fuzzy tuner is proposed in this paper for tuning the parameters of proportional plus integral (PI) controller so that to improve the performance of the SHPF. The compensation process is based on source current sensing only. Synchronous Reference Frame (SRF) theory is used for generating reference currents, whereas linear current controller has been used to track these reference currents. Space Vector Pulse Width Modulation (SVPWM) has been employed to obtain the switching signals required for Voltage Source Converter (VSC). Findings/Improvements: Simulation analysis has been carried out to assess the performance of proposed control scheme. The simulation analysis proved that shunt hybrid power filters to be a potent solution for compensating the harmonics and reactive power of the distribution system. From the Simulation results, total harmonic distortion (THD), steady state response and dynamic behaviour of the fuzzy tuned PI controller based SHPF is found to be better than conventional PI controller.